The Hamilton-Jacobi approach to Teleparallelism - Pimentel, B. M.; Pompeia, P. J.; da Rocha-Neto, J. F. (Societa Italiana Di Fisica, 2005)
We intend to analyse the constraint structure of Teleparallelism employing the Hamilton-Jacobi formalism for singular systems. This study is conducted without using an ADM 3+1 decomposition and without fixing time gauge condition. It can be verified that the field equations constitute an integrable system.